Nasal Carriage of Staphylococcus aureus among Healthy School Children in Kathmandu Valley - Joshi, Dev Raj; Shrestha, Suraj Narayan; Bomjan, Rajdeep; Poudel, Kamal (Nepal Journal of Science and Technology, 2010)
Staphylococcus aureus remains one of the most frequently isolated pathogens in both community and hospital practices. Methicillin resistant S. aureus (MRSA) continues to be a major cause of serious infections in the community worldwide. This study was undertaken to determine the prevalence of S. aureus and MRSA in school children in Kathmandu valley and, also to evaluate the antibiotic susceptibility pattern of the isolates. Identification of the S. aureus was confirmed by standard microbiological methods and the antibiotic susceptibility testing was performed by disk diffusion method according to the Clinical Laboratory Standards Institution (CLSI). Of the 324 school children who participated in the study, 38 (11.8%) had S. aureus isolated from nasal swabs. The potential risk factors for the S. aureus carriage showed the antibiotic usage within past 4 weeks to be associated with the rate of the nasal carriage (p value 0.000). Out of 38, two (5.2%) isolates were MRSA. One of the MRSA strains was also resistant to Cloxacillin. Erythromycin and Cloxacillin resistance was present in 3 (7.9%) isolates. Resistance to two or more antibiotics was noted in 2 (5.3%) isolates. However, no strains were resistant to Vancomycin. The results of this study indicated that the carriage of MRSA exists among young healthy school children who lack traditional risk factors for MRSA. Key words: community acquired MRSA; Staphylococcus aureus; nasal carriage; school children DOI: 10.3126/njst.v9i0.3177 Nepal Journal of Science and Technology 9 (2008) 139-142